Exploring the perception and needs of pharmaceutical care among family caregivers of pediatric asthma patients in Guangdong Province, China: a cross-sectional survey study - Guohua Lin; Dehui Chen; Hao Hu; Carolina Oi Lam Ung (BMC Primary Care)
Abstract Background Asthma brings a huge burden to children and their families. The aim of this study is to investigate the level of understanding of asthma among family caregivers, the burden they facing in caring for children with asthma, and their needs of pharmaceutical care. Methods A questionnaire informed by recent literature was distributed to family caregivers of children (< 18 years old) diagnosed with asthma from Guangdong Province, China. Multiple linear regression analysis was used to identify the factors associated with the caregivers’ need of pharmaceutical care. Results A total of 610 valid questionnaires were collected. Most of the participants were women (60.0%) or aged between 35 and 44 years (48.0%). Only 38.9% of participants believed that they had good asthma related knowledge. There were 59.2% of participants bearing high burden due to pediatric asthma, and 54.9% of the participants indicated great need for pharmaceutical intervention. The results of multiple linear regression showed that pharmaceutical care needs were significantly associated with their gender, age, duration of taking care of pediatric asthma patients, and overall burden (all p < 0.05). Conclusions Caregivers of pediatric asthma patients self-reported inadequate levels of asthma knowledge, high level of burden, and unmet needs for pharmaceutical care, all of which presented great opportunities for pharmacists to contribute to pediatric asthma management at the community level.